Hubungan Body Mass Index dengan Risiko Terjadinya Obstructive Sleep Apnea pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - I Kadek Reynata Wihendra Pasek; Agus Santosa; Ni Wayan Rusni (Aesculapius Medical Journal, 2025)
Obstructive Sleep Apnea (OSA) is a sleep disorder that causes a reduction or blockage of airflow despite efforts to breathe. Body Mass Index (BMI) is one of the indicators used to determine an individual's weight status, whether they are underweight, have an ideal weight, or are overweight (obese). This study aims to determine the relationship between BMI and the risk of OSA among students at the Faculty of Medicine and Health Sciences, Warmadewa University. This is an observational analytical study with a cross-sectional design. The sample was obtained using stratified random sampling with a total of 97 samples. Data collection was done through questionnaires filled out by the respondents to obtain primary data. The independent variable in this study is Body Mass Index (BMI), while the dependent variable is the risk of Obstructive Sleep Apnea (OSA). Data analysis was performed using univariate and bivariate analysis. The correlation between BMI and OSA risk was measured using the Spearman test and crosstab. The results showed that the majority of respondents were male and 19 years old (35.1%), with a normal BMI status (58.8%). A total of 35.1% were at risk of developing OSA based on the Berlin questionnaire, and 64.9% were at risk of OSA based on the ESS questionnaire. The Berlin questionnaire showed a significant and very strong positive correlation between BMI and students at risk of OSA (p = 0.001; r = 0.899). Meanwhile, the ESS questionnaire showed a significant and moderate positive correlation between BMI and OSA risk (p = 0.001; r = 0.442).